Isolation of a small molecule inhibitor of DNA base excision repair. - Madhusudan, S; Smart, F; Shrimpton, P; Parsons, J; Gardiner, L; Houlbrook, S; Talbot, D; Hammonds, T; Freemont, P; Sternberg, M; Dianov, G; Hickson, I (2005)
The base excision repair (BER) pathway is essential for the removal of DNA bases damaged by alkylation or oxidation. A key step in BER is the processing of an apurinic/apyrimidinic (AP) site intermediate by an AP endonuclease. The major AP endonuclease in human cells (APE1, also termed HAP1 and Ref-1) accounts for >95% of the total AP endonuclease activity, and is essential for the protection of cells against the toxic effects of several classes of DNA damaging agents. Moreover, APE1 overexpression has been linked to radio- and chemo-resistance in human tumors. Using a newly developed high-throughput screen, several chemical inhibitors of APE1 have been isolated. Amongst these, CRT0044876 was identified as a potent and selective APE1 inhibitor. CRT0044876 inhibits the AP endonuclease, 3'-phosphodiesterase and 3'-phosphatase activities of APE1 at low micromolar concentrations, and is a specific inhibitor of the exonuclease III family of enzymes to which APE1 belongs. At non-cytotoxic concentrations, CRT0044876 potentiates the cytotoxicity of several DNA base-targeting compounds. This enhancement of cytotoxicity is associated with an accumulation of unrepaired AP sites. In silico modeling studies suggest that CRT0044876 binds to the active site of APE1. These studies provide both a novel reagent for probing APE1 function in human cells, and a rational basis for the development of APE1-targeting drugs for antitumor therapy.